Using acoustic emission methods to monitor cement composites during setting and hardening - Topolář, Libor; Pazdera, Luboš; Kucharczyková, Barbara; Smutný, Jaroslav; Mikulášek, Karel (MDPI AG, 2017)
Cement-based composites belong among the basic building materials used in civil engineering. Their properties are given not only by their composition but also by their behaviour after mixing as well as by the methods of curing. Monitoring the processes and phenomena during the early stages of setting is vital for determining the resulting properties and durability. The acoustic emission method is a unique non-destructive method that can detect structural changes as a cement-based composite is setting. It can also detect the onset and growth of cracks during the service life of a cement-based composite since the moment it has been mixed. The paper discusses the use of the acoustic emission method with focus on the early stage of the lifespan of a cement-based composite including the measures necessary for its use and description of the parameters of acoustic emission signals.

Cement-based composites belong among the basic building materials used in civil engineering. Their properties are given not only by their composition but also by their behaviour after mixing as well as by the methods of curing. Monitoring the processes and phenomena during the early stages of setting is vital for determining the resulting properties and durability. The acoustic emission method is a unique non-destructive method that can detect structural changes as a cement-based composite is setting. It can also detect the onset and growth of cracks during the service life of a cement-based composite since the moment it has been mixed. The paper discusses the use of the acoustic emission method with focus on the early stage of the lifespan of a cement-based composite including the measures necessary for its use and description of the parameters of acoustic emission signals.
Using acoustic emission methods to monitor cement composites during setting and hardening
Keywords: fine-grained cement composite; volume changes; shrinkage; acoustic emission method; fine-grained cement composite; volume changes; shrinkage; acoustic emission method